The Effects of Miscanthus Grass as a Bedding Source and the Dietary Inclusion of Unheated, Low-Trypsin Inhibitor Soybeans on the Performance of Commercial Tom Turkeys Reared to Market Age - C.E. Evans (Journal of Applied Poultry Research, 2019)
SUMMARY: A study was conducted to evaluate bedding source and the inclusion of rolled, unheated soybeans on the growth performance of male turkeys when reared to market age. Pine shavings are the most common poultry bedding material, however recently, increased marketplace competition has significantly reduced its availability and necessitated the need for economical alternatives. Additionally, the development of new varieties of soybeans with low levels of antinutritional factors have created an opportunity for dietary inclusion with minimal processing. The objective of this study was to determine the efficacy of Miscanthus grass as an alternative to pine shavings litter and to evaluate 2 novel, low trypsin inhibitor soybean varieties as a potential ingredient for turkeys. Treatments were arranged in a 2 × 4 factorial design with main effects of litter type (Miscanthus grass or pine shavings) and dietary treatment. Diets were defined based on the soy protein source: LO (novel, unheated low oligosaccharide and trypsin inhibitor soybean), LT (novel, unheated low trypsin inhibitor soybean), SBM (commercial solvent extracted soybean meal), or CB (unheated conventional soybeans). Bedding type did not affect BW gain or feed intake at market, however, a tendency for improved FCR was observed when turkeys were raised on Miscanthus grass (P = 0.073). Turkey toms fed diets containing low trypsin inhibitor soybeans had improved BW gain and feed intake with a lower overall FCR compared to turkeys fed diets containing conventional raw whole soybeans. Therefore, there was improved digestibility of the novel soybean lines. Nutrient utilization of the novel low trypsin inhibitor soybeans, however, remained inferior to diets containing solvent extracted soybean meal, which yielded the heaviest BW and lowest FCR with similar feed intake to the low trypsin inhibitor soybean diets.